2019
DOI: 10.1001/jamaophthalmol.2019.2456
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Industry Payments to Ophthalmologists in the Open Payments Database

Abstract: IMPORTANCE An increased awareness of the interactions between the medical industry and health care professionals may lead to lower health care costs and more effective health care practices. OBJECTIVE To assess the characteristics of industry payments made to ophthalmologists between 2013 and 2017. DESIGN, SETTING, AND PARTICIPANTS This analysis included data reported in the June 29, 2018, update of the Centers for Medicare & Medicaid Services Open Payments Database (OPD). The OPD contains public records of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 26 publications
0
29
1
Order By: Relevance
“…Meanwhile, other studies outside of respiratory specialists reported that there were lower average payments among the US nephrology specialists ($1,795[$2,227 annual general payments) 31 , the US orthopedic surgery ($3,260 in 2013), and the US dermatologists ($4,177) 22 than the Japanese respiratory specialists; while several specialists such as the US ophthalmologists ($5,191) 32 ; the US cardiologists ($5,638) 33 ; the US rheumatologists ($6,444) 34 ; and Japanese respiratory oncologists ($6,992) 19 received higher average payments. Particularly, this study represented large financial relationships of JRS-certified specialists with pharmaceutical companies as compared to other specialists in the US and Japan.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, other studies outside of respiratory specialists reported that there were lower average payments among the US nephrology specialists ($1,795[$2,227 annual general payments) 31 , the US orthopedic surgery ($3,260 in 2013), and the US dermatologists ($4,177) 22 than the Japanese respiratory specialists; while several specialists such as the US ophthalmologists ($5,191) 32 ; the US cardiologists ($5,638) 33 ; the US rheumatologists ($6,444) 34 ; and Japanese respiratory oncologists ($6,992) 19 received higher average payments. Particularly, this study represented large financial relationships of JRS-certified specialists with pharmaceutical companies as compared to other specialists in the US and Japan.…”
Section: Discussionmentioning
confidence: 99%
“…[30]); $25,960 ($5,191 per year) among ophthalmologists between 2013 and 2017 (ref. [41]); $16,914 ($5,638 per year) among cardiologists between 2014 and 2016 (ref. [42]); $38,664 ($6,444 per year) among rheumatologists between 2014 and 2019 (ref.…”
Section: Discussionmentioning
confidence: 99%
“…As previous studies have found (ref. [25, 30, 41–43]), pharmaceutical companies have concentrated their payments on a small number of physicians with extensive clinical and research experience. These specialists, or “key opinion leaders,” (ref.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have been conducted analyzing specialty-specific payment patterns between industry and physicians using the Open Payments database including but not limited to studies on orthopedic surgeons [ 12 ], emergency physicians [ 13 ], pediatricians [ 14 ], neurosurgeons [ 15 ], otolaryngologists [ 18 ], cardiologists [ 19 ], and ophthalmologists [ 20 ]. Additional research has also been conducted to further examine potential physician bias and conflicts of interest within particular specialty areas [ 21 23 ].…”
Section: Discussionmentioning
confidence: 99%